The State of Multimedia Software Today - Shuhrat Akboyevich Kholmurodov; Xudayberdiyev Nortura Kabilovich (Genius Journals, 2022)
In this article, you can get more information about the history of the multimedia program, its mission, content, goals and results
Keywords: video elements; multimedia tools; technical and hardware devices; graphics